(untitled) (Research, Society and Development, 2023)
Introduction: Mental disorders are defined as diseases that manifest psychologically associated with some functional impairment, which encompasses a series of symptoms - such as difficulty concentrating and insomnia. Objective: to describe the nutritional screening and nutritional status of psychiatric patients hospitalized in the Psychiatry sectors of Hospital de Clínicas Gaspar Vianna (HCGV). Methodology: Cross-sectional descriptive and analytical study, with hospitalized patients with mental disorders. For statistical analysis, the Spearman correlation test was used and a 5% significance level was adopted. Results: Ninety-four patients were evaluated, of which 58.24% were male and 41.75% were female, of which 95.60% were adults. According to the BMI, the prevailing nutritional status was eutrophy (51.64%), whereas, according to the %ACB, it was malnutrition (49.45%). Conclusion: The use of subjective and objective methods with these patients is extremely important to define the best nutritional practices and thus guarantee the recovery or maintenance of the nutritional status of these individuals.